2016
DOI: 10.3389/fimmu.2016.00497
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms That Underlie the Dynamic Adaptation of Innate Monocyte Memory to Varying Stimulant Strength of TLR Ligands

Abstract: In adaptation to rising stimulant strength, innate monocytes can be dynamically programed to preferentially express either pro- or anti-inflammatory mediators. Such dynamic innate adaptation or programing may bear profound relevance in host health and disease. However, molecular mechanisms that govern innate adaptation to varying strength of stimulants are not well understood. Using lipopolysaccharide (LPS), the model stimulant of toll-like-receptor 4 (TLR4), we reported that the expressions of pro-inflammator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
62
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(69 citation statements)
references
References 43 publications
7
62
0
Order By: Relevance
“…The magnitude of the immune response is dependent on the strength of the external stimulus. LPS (endotoxin) is part of the outer membrane of Gram‐negative bacteria and a potent activator of immune cells . LPS induces a robust inflammatory response after its recognition by the myeloid differentiation protein (MD)2, TLR4, and cluster of differentiation (CD)14 macromolecular complex .…”
Section: Introductionmentioning
confidence: 99%
“…The magnitude of the immune response is dependent on the strength of the external stimulus. LPS (endotoxin) is part of the outer membrane of Gram‐negative bacteria and a potent activator of immune cells . LPS induces a robust inflammatory response after its recognition by the myeloid differentiation protein (MD)2, TLR4, and cluster of differentiation (CD)14 macromolecular complex .…”
Section: Introductionmentioning
confidence: 99%
“…We recently reported that defective completion of the autophagy process via disruption of autolysosome fusion may skew innate monocytes into a nonresolving inflammatory state with elevated expression of selective inflammatory mediators [7]. Disrupted autolysosome fusion may cause an accumulation of inflamed autophagosomes triggering activation of the transcription factor IRF5 [7,15]. We also identified Tollip as a key mediator in the proper formation of the autolysosome [48].…”
Section: Cellular Mechanisms For Innate Leukocyte Programming Dynamicsmentioning
confidence: 96%
“…These negative regulators may attenuate cellular signaling, as well as epigenetically remodel and suppress selected chromatin associated with the expression of proinflammatory mediators [13,14]. In addition to endotoxin, TLR7 and TLR9 agonists may similarly induce monocyte tolerance with similar molecular mechanisms [15,16].…”
Section: Molecular Mechanisms For Programming Dynamics Of Innate Leukmentioning
confidence: 99%
See 2 more Smart Citations